Role of Ayurveda in the Management of Alcohol Addiction: A Case Report - sharma , Monika; prasad bairwa , Jagdish; goyal, Swati (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: When significant doses of ethyl alcohol beverages are consumed on a regular basis for an extended period of time and are accompanied by a morbid need to drink alcohol, it is considered alcohol addiction. Main Clinical Findings: A 45-year-old male who had been drinking for 5 years took a 3-day break. As a result, he began to experience anxiety, weakness, tremors, decreased appetite, and weariness as symptoms of alcohol addiction, along with disrupted mental status and sleep.